Strategy for Improving The Work Discipline of Village Apparatus in Sidenreng Rappang Regency - Pratiwi Ramlan; Sapri Tajuddin; Khaeriyah Adri; Mardhatillah Devi Febrianti (Indonesian Association for Public Administration (IAPA), 2020)
The purpose of this study was to analyze and determine strategies for improving the work discipline of village officials in Sidenreng Rappang Regency. This research was conducted in Carawali Village, Sidenreng Rappang Regency. The method used in this research is a qualitative approach (qualitative research). Data collection was carried out by means of observation and in-depth interviews. The primary data source in this study consisted of key informants, namely the Head of the Carawali Village and the informants in this study were officials / employees of the Carawali Village, Sidenreng Rappang District, obtained through the purposive sampling method. The data analysis technique uses the SWOT analysis method which is one of the methods used to describe the condition of a problem, and evaluate the problem, which is based on internal and external factors, namely Strengths, Weaknesses, Opportunities and Threats which then create a matrix. and assessment to find out the most appropriate strategy. Based on the results of this study, the most appropriate strategy to improve the work discipline of the Carawali Village Officials in Sidenreng Rappang District is to improve village apparatus services by conducting leadership training, utilizing human resources to participate in training in improving quality to use information system technology, improving coordination and supervision of village heads with other village officials, making clear SOPs on the rules and salary system to be applied.